Regeneration of Transgenic Rice with Bacterial ipt Gene Driven by Senescence Specific (SAG12) Promoter by Particle Bombardment - Santosini Devi,; Manoj K Mishra,; Malcolm Elliott, (Tropical Life Sciences Research, 2012)
Transgenic rice plants were generated using particle bombardment to introduce the Agrobacterium cytokinin biosynthesis gene driven by Arabidopsis (Arabidopsis thaliana) senescence specific promoter (SAG12) for delaying leaf senescence. Using two plasmids we co-transformed one week old embryogenic calli derived from mature Japonica rice (Oryza sativa) variety Chin Guang. The selectable marker hygromycin phosphotransferase (hph) gene and the reporter gene B-ß-glucuronidase (uidA), both under the control of cauliflower mosaic virus (CaMV) 35S promoter were placed on the same co-integrate vector whereas the cytokinin biosynthesis gene, isopentenyl transferase (ipt) driven by the SAG12 promoter is supplied in another plasmid. A total of 32 transgenic rice plants were regenerated of which 27 plants were randomly selected for histochemical ß-glucuronidase (GUS) assay, PCR and Southern blot analysis. Cointegration frequencies of 88% and 69% were obtained for two linked genes (uidA and hph) and two unlinked genes (hph and ipt gene) respectively in R0 plants. Southern blot analysis confirmed the results of histochemical GUS assay and PCR amplifications. A complex integration pattern for all the transgenes including the multiple copies integration was predominantly observed. Pokok padi transgenik telah dijanakan menggunakan pembedilan partikel untuk memperkenalkan gen biosintesis sitokinin Agrobacterium yang dipacu oleh promoter spesifik kesenesensan Arabidopsis (Arabidopsis thaliana) iaitu SAG12, yang berfungsi untuk melengahkan kesenesensan daun. Dengan menggunakan dua plasmid, kalus embriogeni berumur satu minggu yang diambil dari padi Japonica (Oryza sativa) varieti Chin Guang matang telah ditransformasi. Gen penanda memilih hygromycin phosphotransferase (hph) dan gen reporter B-ß-glucuronidase (uidA) yang kedua-duanya dikawal oleh promoter cauliflower mosaic virus (CaMV) 35S, telah diletakkan pada vektor co-integrate manakala gen biosintesis sitokinin, isopentenyl transferase (ipt) yang dipacu oleh promoter SAG12 telah dibekalkan dalam plasmid yang lain. Tiga puluh dua pokok padi transgenik telah dijana; 27 pokok telah dipilih secara rawak untuk cerakin histokimia ß-glucuronidase (GUS), PCR dan analisis sap Southern. Frekuensi co-integration sebanyak 88% dan 69% telah diperolehi untuk dua gen terangkai (uidA and hph) dan dua gen tidak terangkai (hph and ipt gene) masing-masing dalam pokok R0. Analisis sap Southern telah mensahkan keputusan cerakin histokimia GUS dan amplifikasi PCR. Satu corak integrasi yang kompleks untuk semua transgen termasuk integrasi salinan berbilang telah diperhatikan.